2010
DOI: 10.2215/cjn.01030210
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Proteinuria in an Injection Drug User Population

Abstract: Background and objectives: Proteinuria is a major determinant of chronic kidney disease. We aimed to characterize the prevalence and correlates of proteinuria in a cohort of HIV-infected and uninfected injection drug users.Design, setting, participants, & measurements: A cross-sectional analysis was performed among 902 injection drug users (273 HIV-infected) in the AIDS Linked to the Intravenous Experience cohort. The primary outcome was proteinuria defined as having a urine protein/creatinine concentration ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…Two studies defined proteinuria by standard dipstick urinalysis [30,33], and four measured albuminuria by spot urine albumin/creatinine ratio [27,29,32,34]. The summary estimate for adjusted OR of proteinuria with HCV was 1.508 (95 % CI 1.19; 1.89, P = 0.0001) across the identified studies (Fig.…”
Section: Summary Estimate Of Outcome: Prevalence Of Proteinuriamentioning
confidence: 97%
See 3 more Smart Citations
“…Two studies defined proteinuria by standard dipstick urinalysis [30,33], and four measured albuminuria by spot urine albumin/creatinine ratio [27,29,32,34]. The summary estimate for adjusted OR of proteinuria with HCV was 1.508 (95 % CI 1.19; 1.89, P = 0.0001) across the identified studies (Fig.…”
Section: Summary Estimate Of Outcome: Prevalence Of Proteinuriamentioning
confidence: 97%
“…The studies were published in 17 various articles [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and carried out in 4 countries ( Fig. 1) (n = 2,842,421 unique patients).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of proteinuria in adults in the general population in the US ranges from 6–10%, 14,15 while various studies in the US and abroad have demonstrated a higher prevalence of proteinuria in HIV-infected adults ranging from 17–45% 16,17 and 21–33% in children. 18,19 Likewise, due to the significant limitations of serum creatinine-based glomerular filtration rate (GFR) estimation in individuals with HIV, serum cystatin C has emerged as a marker for both the evaluation of GFR and the detection of drug-induced kidney injury.…”
Section: Introductionmentioning
confidence: 99%